2009
DOI: 10.1007/s11707-009-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on sustainable water use of the Haihe River Basin using ecological network analysis

Abstract: Sustainable water use of the Haihe River Basin is studied by using the ecological network analysis (ENA) approach. Two related aspects including socioeconomic and environmental water uses sustainability and network organization inherent in system structures are analyzed. For the study of sustainable water use from each single aspect including water use intensity, water use pressure, and environmental protection, a series of new indicators termed as total system throughput water use intensity (TSTUI), total sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, in 2016, the Chinese Environmental Minister reported that each percentage point increase in the urbanization rate resulted in 1.15 billion tons of extra sewage. In addition, urban areas with higher living standards demand more freshwater than rural areas (Li and Chen, 2009), e.g., in 2018, domestic water use per capita was 225 L/d in China's urban areas while it was 89 L/d in rural areas.…”
Section: Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 2016, the Chinese Environmental Minister reported that each percentage point increase in the urbanization rate resulted in 1.15 billion tons of extra sewage. In addition, urban areas with higher living standards demand more freshwater than rural areas (Li and Chen, 2009), e.g., in 2018, domestic water use per capita was 225 L/d in China's urban areas while it was 89 L/d in rural areas.…”
Section: Urbanizationmentioning
confidence: 99%
“…On one hand, a growing population expands the scale of economic activities and thus generates the economies of scale (Li et al, 2019), which increases the water-use productivity to some extent. On the other hand, water consumption and wastewater discharge can increase rapidly with population growth as daily activities cannot be separated from the water resources (Li and Chen, 2009).…”
Section: Population Scalementioning
confidence: 99%
“…The interdisciplinary nature of water resources problems requires the integration several aspects including economic, environmental, social, and legal aspects into a coherent analytical framework [11][12][13]. Some basin-scale water use frameworks were constructed to search the balance points among different sectors [14,15]. For example, socio-economic water sectors were included in the framework to detect the interactions among various sectors.…”
Section: Introductionmentioning
confidence: 99%